ASSESSING PLANT CONSUMPTION AND USE AMONG MARINE HUNTER GATHERERS AND FISHERS THROUGH DENTAL CALCULUS STUDIES OF THE NORTHERN PATAGONIAN CHANNELS (41°30′-47° S) - Belmar, Carolina A.; Reyes, Omar; Albornoz, Ximena; Tessone, Augusto; San Roman Bontes, Manuel Julio; Morello Repetto, Flavia; Urbina, Ximena (My University, 2021)
This paper presents the results of the study of the microfossil content of the human dental calculus of 49 individuals from 17 archaeological sites of the Chiloe and Los Chonos archipelago with chronologies between similar to 4400 to 300 years cal BP. The previous delta C-13 and delta N-15 stable isotope values of the inhabitants of this area revealed an eminently marine diet for these hunter gatherers. Nevertheless, in relation to their predominant diet, the consumption of plant resources has remained unseen. The integration of this type of evidence has allowed us to detect the consumption of seaweed, wild and domesticated plants, some with medicinal and psychoactive properties, in addition to the functional use of the oral cavity based on the presence of remains of plant stems used in basketry. Finally, the presence of domesticated plants in the northern archipelagos constitutes a bio-indicator of archaeological remains that allows us to project contacts between different cultural pathways of the marine hunter gatherers and horticultural groups throughout the temporal sequence.
Keywords: western patagonian channels; middle/late holocene; diet; marine hunter gatherers; human tooth calculus; paleoethnobotany